Under Threat: Rules-Based Fiscal Policy and How to Preserve It - Xavier Debrun; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2018)
Rules-based fiscal policy is under threat. Over the last two decades, it proved frustratingly complicated to strike the right balance between three essential properties of sound fiscal policy rules: simplicity, flexibility, and enforceability. Simplicity has been sacrificed to ensure that more contingent (i.e. flexible) rules remained enforceable. The resulting arrangements have failed to adequately guide fiscal policy, undermining formal compliance, and ultimately, popular and political support for rules. To mitigate the risk that countries abandon rules-based policymaking, we suggest downplaying enforceability—i.e. the role of formal sanctions through enforcement—and enhancing the reputational costs of breaching rules. At the limit, the rule could consist of a simple quantitative benchmark for a key fiscal indicator. To boost reputational effects, independent fiscal councils should focus on debunking the "fiscal alchemy", clearing the public debate from partisan smokescreens, and fostering popular support for sound fiscal policies.
Keywords: E62; F42; F61; 330; Fiscal policy rules; Euro area; fiscal policy; independent fiscal councils